Pengaruh Infrastruktur terhadap Pertumbuhan Ekonomi di Provinsi Jawa Tengah - Kamilla, Saadatul; Hutajulu, Dinar Melani (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
ABSTRACT One of the most important aspects in economic development is infrastructure. Adequate and equitable infrastructure in all regions of a country will facilitate economic performer in accessing and carrying out economic activities. A good economic activities will create economic growth. The main purpose of this research is to know the effect of infrastructure on economic growth. The study was conducted in Central Java province using secondary data from 2006-2018. The independent variable of this study is the basic infrastructure including roads, electricity and water. While the dependent variable is the GRDP. The model used is multiple linear regression model using time series data. The results of this study indicate that the road infrastructure variable is significant to influence on economic growth. The variable infrastructure of electricity shows significant results and have a positive effect on economic growth. Variable infrastructure of water shows the results are insignificant on economic growth. Keywords: economic growth, road, electricity, water